2008
DOI: 10.1029/2008gl035987
|View full text |Cite
|
Sign up to set email alerts
|

Flood trends and river engineering on the Mississippi River system

Abstract: .[1] Along >4000 km of the Mississippi River system, we document that climate, land-use change, and river engineering have contributed to statistically significant increases in flooding over the past 100-150 years. Trends were tested using a database of >8 million hydrological measurements. A geospatial database of historical engineering construction was used to quantify the response of flood levels to each unit of engineering infrastructure. Significant climate-and/or land use-driven increases in flow were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 24 publications
(27 reference statements)
2
87
0
1
Order By: Relevance
“…Based on hydraulic principles, Yen (1995) found that for a given flood, levees raise the stage in the channel adjacent to a levee and upstream of it. On the MMR, Pinter et al (2008Pinter et al ( , 2010 and Remo et al (2009) found that levee construction was the second most important contributor to historical flood-level increases, after channel training structures. Dyhouse (1985) assessed the impact of agricultural levees on MMR flood stages, suggesting a 1.5-m levee-driven increase for the 100-year flood.…”
Section: Infrastructurementioning
confidence: 97%
See 3 more Smart Citations
“…Based on hydraulic principles, Yen (1995) found that for a given flood, levees raise the stage in the channel adjacent to a levee and upstream of it. On the MMR, Pinter et al (2008Pinter et al ( , 2010 and Remo et al (2009) found that levee construction was the second most important contributor to historical flood-level increases, after channel training structures. Dyhouse (1985) assessed the impact of agricultural levees on MMR flood stages, suggesting a 1.5-m levee-driven increase for the 100-year flood.…”
Section: Infrastructurementioning
confidence: 97%
“…Several studies over the past 35 years have concluded that stages for large floods (i.e., C100-year recurrence interval) have risen by as much as *4 m along the MMR, driven primarily by the intensive use of wing dikes and other river training structures to facilitate navigation (Belt 1975;Stevens et al 1975;Criss and Shock 2001;Pinter et al 2000Pinter et al , 2001Pinter et al , 2008Remo and Pinter 2007;. Belt (1975) concluded that constricting the river channel increases flood levels and reducing the protection provided by levees.…”
Section: Infrastructurementioning
confidence: 97%
See 2 more Smart Citations
“…Characteristics of each levee-failure site were derived from digital elevation model (DEM) data, surficial geologic maps (Fisk, 1944;Saucier, 1994), and soil survey maps (NRCS, 2008). In addition, various river engineering records and related data (assembled and described in Pinter et al, 2008Pinter et al, , 2010; see also Table 1) were used to identify locations of levee scour and repairs, local dredging activity, river constriction over time, and revetment locations. Historical land-cover data, riparian corridor information, location of borrow pits, channel width, floodplain width, and channel sinuosity were obtained from the maps identified in Table 1.…”
Section: Data Sourcesmentioning
confidence: 99%